The effects of tapering on power-force-velocity profiling and jump performance in professional rugby league players - de Lacey, J.; Brughelli, M.; McGuigan, M.; Hansen, K.; Samozino, P.; Morin, J.-B. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to investigate the effects of a preseason taper on individual power-force-velocity profiles and jump performance in professional National Rugby League players. Seven professional rugby league players performed concentric squat jumps using ascending loads of 25, 50, 75, 100% body mass before and after a 21-day step taper leading into the in-season. Linear force-velocity relationships were derived, and the following variables were obtained: maximum theoretical velocity (V0), maximum theoretical force (F0), and maximum power (Pmax). The players showed likely-to-very likely increases in F0 (effect size [ES] = 0.45) and Pmax (ES = 0.85) from pre to posttaper. Loaded squat jump height also showed likely-to-most likely increases at each load (ES = 0.83-1.04). The 21-day taper was effective at enhancing maximal power output and jump height performance in professional rugby players, possibly as a result of a recovery from fatigue and thus increased strength capability after a prolonged preseason training period. Rugby league strength and conditioning coaches should consider reducing training volume while maintaining intensity and aerobic conditioning (e.g., step taper) leading into the in-season.